PENGARUH POSITIF PENGAJIAN RUTIN TERHADAP NILAI IBADAH MASYARAKAT DI JORONG PANINJAUAN KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - Putri Ayuni (Yayasan Baitul Hikmah al-Zain, 2024)
Social function is something that can be enjoyed and useful for people's lives or that has something to do with people's lives. What is meant by the social function of routine recitation is a community activity to deepen the teachings of the Islamic religion which can be beneficial for people's lives which is routinely carried out in turns or in turns at people's homes. Busyness and work cause the people of Jorong Paninjauan to be less able to fulfill their spiritual needs because they have to carry out their duties and responsibilities. However, they still need space for spirituality and religious guidance. To be able to meet these needs, of course, in a very easy and time-saving way. The reality on the ground is that Muslim women carry out recitations in turns at people's homes and have other functions than religious recitations, namely social functions.